THE ROLE OF TAXES IN REGULATING HOUSEHOLD INCOME (International journal of artificial intelligence, 2026)
This article examines the role of taxation as a key instrument of state economic policy in regulating household income and ensuring social equity. The study analyzes the mechanisms through which tax systems influence income distribution, including progressive taxation, tax benefits, and social transfers. Particular attention is paid to the impact of direct and indirect taxes on different income groups, as well as their role in reducing income inequality and poverty. The paper also explores international practices in tax regulation and evaluates their applicability within the context of developing economies, including Uzbekistan. The findings suggest that an effective and well-balanced tax policy contributes significantly to income redistribution, social stability, and sustainable economic development. Recommendations are proposed to improve the efficiency of tax instruments in achieving equitable income distribution.